Reports and the their annexes prepared by the European anti-fraud office in the pre-trial criminal proceedings - Madzharov, Ivan (Law Journal of New Bulgarian University, 2022)
The article is related to а specific procedure – the inclusion and application of the reports and their annexes prepared by the European anti-fraud office (OLAF) in the Bulgarian pre-trial proceedings. The reports and their annexes are prepared according to Regulation 883/2013 which regulates all the activities of OLAF in the EU and third countries. The reports and their annexes are a specific tool for our legislation and they can be used in the pre-trial proceedings as written proof tools according to the Bulgarian Criminal Procedure Code. This article explains the OLAF’s structure and the practical application of the OLAF’s reports and their annexes during the pre-trial investigation and focuses on the main problems which are encountered in the investigation practice related to their application as well.